Effect of Vesicle Structure on Catalytic Activity of Suzuki‐Miyaura Cross‐Coupling Reaction: Impact of Framework and Morphology. Issue 37 (1st October 2020) - Song, Kunpeng; Jiang, Yaya; Zou, Zhijuan
Abstract: A novel hybrid porous polymer with hollow vesicle structure has been synthesized via Friedel‐Crafts alkylation reaction and solvent‐induced method. The resulting two‐dimensional networks are hierarchical porous materials with high Brunauer‐Emmett‐Teller (BET) surface area of 1582 m 2 g −1 . The vesicle structure directly influenced the activity and shaping the performance of the catalyst. The kinetic study reveals the special vesicle structure can enrich the substrates in a limit scope and increase the reaction rate. It has been demonstrated that the framework and morphology play a major role on the catalysts' excellent performance in Suzuki–Miyaura cross‐coupling reaction of aryl chlorides. These findings help elucidate the mode action of the vesicle structure in the unrevealed Suzuki reaction mechanism of supports and the potential development of new morphology control catalysts. Abstract : A novel hollow vesicle structure catalyst was reported, the diameter of vesicles and pore size distribution of catalyst have a positive influence on the catalytic activity in Suzuki–Miyaura cross‐coupling reaction of aryl chlorides.